2022
DOI: 10.1093/neuonc/noac286
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule-mediated disruption of ribosome biogenesis synergizes with FGFR inhibitors to suppress glioma cell growth

Abstract: Background High-grade gliomas are malignant brain tumors characterized by aggressiveness and resistance to chemotherapy. Prognosis remains dismal, highlighting the need to identify novel molecular dependencies and targets. Ribosome biogenesis (RiBi), taking place in the nucleolus, represents a promising target as several cancer types rely on high RiBi rates to sustain proliferation. Publicly available transcriptomics data of glioma patients revealed a positive correlation between RiBi rates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Our previous studies using BMH-21 confirmed that it is a potent inhibitor of Pol I, ribosome biogenesis and induces cell death. Notably, analysis of gene expression in BMH-21-treated cells indicated an unexpectedly great number of genes with perturbed expression, suggesting effects and targets beyond the inhibition of Pol I ( 19 , 20 ). Hence, it is necessary to better understand the mechanism of action of BMH-21 and how transcription is affected.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies using BMH-21 confirmed that it is a potent inhibitor of Pol I, ribosome biogenesis and induces cell death. Notably, analysis of gene expression in BMH-21-treated cells indicated an unexpectedly great number of genes with perturbed expression, suggesting effects and targets beyond the inhibition of Pol I ( 19 , 20 ). Hence, it is necessary to better understand the mechanism of action of BMH-21 and how transcription is affected.…”
Section: Introductionmentioning
confidence: 99%